Targeting in Language: Unifying Deixis and Anaphora - Talmy, Leonard (Frontiers in Psychology, 2020)
This article proposes that a single cognitive system underlies the two domains of linguistic reference traditionally termed anaphora and deixis. In anaphora, the referent is an element of the current discourse itself, whereas in deixis, the referent is outside the discourse in its spatiotemporal surroundings. This difference between the lexical and the physical has traditionally led to distinct theoretical treatments of such referents. We propose instead that language engages a single linguistic/cognitive system—“targeting”—to single out a referent whether it is speech-internal or speech-external. To outline this system: As a speaker communicates with a hearer, her attention can come to be on something in the environment—her “target”—that she wants to refer to at a certain point in her discourse. This target can be located near or far in either the speech-external(deictic) or the speech-internal (anaphoric) environment. She thus needs the hearer to know what her intended target is and to have his attention on it jointly with her own at the relevant point in her discourse. The problem, though, is how to bring this about. Language solves this problem through targeting. First, at the intended point in her discourse, the speaker places a “trigger”—one out of a specialized set of mostly closed-class forms. English triggers include: this/these, that/those, here, there, yonder, now, then, therefore, thus, so, such, yay, the, personal pronouns, relative pronouns, and tense markers. Next, on hearing the trigger, the hearer undertakes a particular three-stage procedure. In the first stage, he seeks all available “cues” to the target. Such cues belong to ten distinct categories, representing ten different sources of information about the target. In the second stage, he combines these cues so as to narrow down to the one intended target and rule out alternative candidates. In the third stage, he maps the concept of the target he has found back onto the original trigger for integration with the sentence’s overall reference. This article is based on the overview portion of a book—The Targeting System of Language, MIT Press, 2018.